Financing of Micro Small and Medium Enterprise Sector In India: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The contribution of Micro-Small and Medium Enterprises (MSMEs) has beengrowing tremendously in the overall industrial economy of the country. Inrecent times, the MSME sector has consistently shown a higher growth ratecompared to the overall industrial sector. In the Indian market, MSME’s rapidgrowth is shown by the Indian entrepreneurs making remarkable progress invarious Industries like Manufacturing, Precision Engineering Design, FoodProcessing, Pharmaceutical, Textile & Garments, Retail, Agro and Servicesector. MSMEs complement and go hand in hand with these large industries asancillary units and contribute largely to the socioeconomic development of thecountry. However, although MSME’s contribution is phenomenal in the growth ofIndian economy, but still; they are facing intense pressure and constraints tosustain their competitiveness in a globalized world. MSMEs in India are facingissues such as the recession, low demand, finance, heavy competition from MNCsetc. But majorly, the availability of external finance for them is a matter ofimportance for policy makers around the globe.